Rural Nonfarm Employment and Incomes in the Eastern Himalayas - Dil Bahadur Rahut; Maja B. Micevska (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
Nonfarm activities generate on average about 60 percent of rural households? incomes in the eastern Himalayan region of India. This paper analyzes the determinants of participation in nonfarm activities and of nonfarm incomes across rural households. We present and explore an analytical framework that yields different activity choices as optimal solutions to a simple utility maximization problem. A unique data set collected in the eastern Himalayas allows us to closely examine the implications of the analytical framework. We conduct an empirical inquiry that reveals that education plays a major role in accessing more remunerative nonfarm employment. Other household assets and characteristics such as land, social status, geographical location, and credit access also play a role.
Keywords: Q12; O18; O15; R11; 330; Nonfarm employment; Rural households; Incomes; Education; India